Topoisomerase II inhibitors in AML: past, present, and future. (2nd September 2019) - Economides, Minas P.; McCue, Deborah; Borthakur, Gautam; Pemmaraju, Naveen
ABSTRACT: Introduction : Topoisomerase II inhibitors have long been used in the frontline and as salvage therapy for AML, with daunorubicin and idarubicin being prototypical agents in this therapeutic class, classically in combination with nucleoside analogs, e.g. cytarabine. Most recently, several other compounds from this drug class have or are being investigated. Areas covered : The current paper reviews older and newer topoisomerase II inhibitors in clinical development for the treatment of AML. The authors discuss the clinical use of these agents, current trials involving them as well as their safety profile. Important side effects of these medications including therapy-related AML (t-AML) are also covered. Expert opinion : Topoisomerase II inhibitors have helped improve outcomes in AML. Recently, the FDA approved several agents including CPX-351 for the treatment of secondary and t-AML. CPX-351 may have applicability in other high-risk myeloid diseases. Future directions include a combination of these agents with other targeted therapies. Finally, the authors believe that small molecule inhibitors, such as venetoclax and possibly immunotherapy options could also be incorporated to our treatment paradigm in selected patients.